Development of Side Bidirectional Leader and Its Effect on Channel Branching of the Progressing Positive Leader of Lightning. Issue 3 (1st February 2019) - Yuan, Shanfeng; Jiang, Rubin; Qie, Xiushu; Sun, Zhuling; Wang, Dongfang; Srivastava, Abhay
Abstract: Fine time‐resolved images of the development of lightning bidirectional leaders below the cloud base were captured by a high‐speed camera in association with multiband electromagnetic field measurements. The bileaders tended to originate at a radial distance of about 200 m from a progressing positive leader channel, propagating more or less radially toward and away from the main channel. Significant asymmetrical channel extensions at opposite ends were clearly recognized. The positive ends of the bileaders propagated in single paths with average speed of 6.1 × 10 4 m/s, while the opposite negative end involved obvious branching and stepping propagation with average speed of 1.6 × 10 5 m/s. The bidirectional leaders eventually connected to the existing main positive leader, producing new branches of the flash. Another cause of positive leader branching was that the positive leader split at its head and developed into different branches synchronously, which were sometimes invisible but were revealed by recoil leaders. Plain Language Summary: A fundamental issue of lightning physics concerns the generation and propagation of leaders that eventually establish the channels of a lightning discharge. Recent research has arrived at a common understanding of the considerable differences of lightning leaders of positive and negative polarities. However, the details of positive leader development are still not well understood. Here we report the fine time‐resolved images of the floating bidirectional leaders initiating near a progressing positive leader. Asymmetrical features at the opposite ends of the bileaders were clearly identified. The stepping and branching negative ends eventually connected to the existing main channel, while the positive ends propagated radially outward with single paths. These processes lead to the formation of new branches to the lateral side of the main positive leader channel. Another scenario for positive leader branching was the head splitting directly and developing synchronously, and the process was sometimes invisible, but could be revealed clearly by subsequent recoil leader events. Key Points: Fine time‐resolved images revealed propagation of bidirectional leaders acting as side discharges of a progressing main positive leader By connecting to the parent positive leader, the bidirectional side discharges are a cause of major branches in positive breakdown The head of a positive leader can split directly to form branches, which may be weak but can be revealed by recoil leaders